A Novel Method for Vector Control of Three-Phase Induction Motor under Open-Phase Fault - Jannati, Mohammad; Asgari, Seyed Hesam; Nik Idris, Nik Rumzi; Bin Abdul Aziz, Mohd Junaidi (ITB Journal Publisher, LPPM ITB, 2015)
The majority of electrical machines such as induction motors can be modeled by an equivalent two-phase machine model (d-q model). A three-phase induction motor withÂ one of the stator phasesÂ openedÂ (faulty three-phase induction motor) can be also modeled by an equivalent two-phase machine. If a conventional vector control method for balanced three-phase induction motors is used for this faulty machine, significant oscillations in speed and torque will result. In this paper, a novel technique for vector control of faulty three-phase induction motors based on rotor-field oriented control (RFOC) is presented. The performance of the proposed method was evaluated using MATLAB software. The results show that it achieves significant improvements in the oscillation reduction of the speed and torque responses.